Metal isotope complexation with environmentally relevant surfaces: Opening the isotope fractionation black box. Issue 20 (18th October 2022) - Komárek, Michael; Ratié, Gildas; Vaňková, Zuzana; Šípková, Adéla; Chrastný, Vladislav
Abstract: The number of studies using various stable isotope systems for tracing contamination sources and various biogeochemical processes is rapidly rising due to the increased availability of the techniques used for isotope analyses. However, in most cases, the resulting isotope data are influenced by many processes occurring within reactive environmental compartments, e.g., soils and sediments, such as sorption, precipitation, redox changes, interactions with plants and microorganisms, etc. Therefore, isotope tracing becomes challenging as it is crucial to identify and quantify the isotope fractionation extent during separate processes in this so-called "isotope fractionation black box". The main aim of this review is to (i) summarize literature data on fractionation of selected metal isotopes (Cd, Cu, Hg, Ni, Zn) after complexation with relevant environmental surfaces, e.g., oxyhydroxides, clay minerals, natural organic matter etc., (ii) briefly describe the analytical techniques and key procedures used for the determination of such data and (iii) provide suggestions and perspectives for future research, including a critical evaluation of specific issues related to isotope analyses and especially the interpretation of results. For example, concentration equilibrium usually differs from isotope fractionation equilibrium, metal coordination chemistry in solution is crucial to decipher metal isotopic fractionation, spectroscopic data are missing, different experimental conditions are often and potential precipitation and desorption reactions are not always considered, etc. Consistent presentation of adsorption/complexation data would also be highly beneficial in future studies. Graphical abstract: UF0001